Vascular Health in Kawasaki Disease - Selamet Tierney, Elif Seda; Gal, Dana; Gauvreau, Kimberly; Baker, Annette L.; Trevey, Shari; O'Neill, Stephen R.; Jaff, Michael R.; de Ferranti, Sarah; Fulton, David R.; Colan, Steven D.; Newburger, Jane W. (Journal of the American College of Cardiology, 2013)
The objective of our study was to compare the indices of vascular health in Kawasaki disease (KD) patients to those of control subjects. The literature on peripheral vascular health after KD is conflicting. Subjects were patients 11 to 29 years of age with the onset of KD >12 months before the study visit (n = 203) and healthy control subjects (n = 50). We measured endothelial function (using the Endothelial Pulse Amplitude Testing index), intima-media thickness (IMT) of the right common carotid artery (RCCA) and the left common carotid artery (LCCA), and fasting lipid profile and C-reactive protein (CRP). KD patients were classified according to their worst-ever coronary artery (CA) status: group I, always normal CAs (n = 136, 67%); group II, CA z-scores ≥2 but <3 (n = 20, 10%); group III, CA aneurysm z-scores ≥3 but <8 mm (n = 40, 20%); and group IV, giant CA aneurysm, defined as ≥8 mm (n = 7, 3%). At a median of 11.6 years (range, 1.2 to 26 years) after KD onset, compared with controls, KD patients had a higher peak velocity in the LCCA (p = 0.04) and higher pulsatility index of both the RCCA and LCCA (p = 0.006 and p = 0.05, respectively). However, there were no differences in the Endo-PAT index or carotid IMT or stiffness. The mean IMT of the LCCA tended to differ across the KD subgroups and control group (p = 0.05), with a higher mean in group IV. Otherwise the KD subgroups and control group had similar vascular health indexes. In contrast to some earlier reports, our study of North American children and young adults demonstrated that KD patients whose maximum CA dimensions were either always normal or mildly ectatic have normal vascular health indexes, providing reassurance regarding peripheral vascular health in this population.